THE PROS AND CONS OF ARTIFICIAL INTELLIGENCE - Turaev Takhir Yuldashovich; Madayeva Muqaddas Bakhtiyor qizi (Web of Journals Publishing, 2025)
This article comprehensively analyzes the role of artificial intelligence (AI) technologies in society, their positive and negative aspects. In recent years, artificial intelligence has been deeply penetrating almost all areas of science, technology, economics, education, medicine, and everyday life. This technology, which imitates human intelligence, has great potential, but also poses certain risks and problems. The article emphasizes the positive aspects of artificial intelligence, including increasing work efficiency, quickly and accurately solving complex problems, and reducing errors due to the human factor. In particular, AI plays an important role in the early detection of diseases, improving diagnostic and treatment processes in the medical field. In education, the possibilities of individualizing the learning process, developing distance learning, and quickly analyzing knowledge are expanding. Also, saving time and resources through automation in production and industry, and increasing economic efficiency are among the important advantages of artificial intelligence.
Keywords: Artificial Intelligence, Machine Learning, Deep Learning, Automation, Ethical Challenges, Algorithmic Bias, Data Privacy, Information Security, Decision-Making Systems, Technological Innovation, Social Impact, Economic Development, Labor Market Transformation, Job Displacement, Human–Machine Interaction, Responsible AI, Governance Frameworks, Transparency and Accountability, Digital Transformation, Sustainable Development.